“SWINGING HEART” IN A SEVERELY HYPOTHYROID PATIENT: A CASE REPORT - Tan, Yee Ling; WA, Siti Sanaa; MA, Masliza Hanuni; R, Ahmad Wazi; MI, Johari (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Introduction Hypothyroidism is a disorder with multiorgan involvement that may lead to various complications. Pericardial effusion is commonly seen in cases of severe hypothyroidism, which may deteriorate into life-threatening cardiac tamponade. Early diagnosis and management of pericardial effusion in hypothyroidism is crucial. Case A 45-year-old female was brought to the emergency department with breathlessness and pleuritic chest pain. She had a background history of diffuse large B-cell lymphoma of the thyroid gland stage 2Bx. She had achieved complete remission for the past year following thyroidectomy and a full course of chemotherapy in December 2022. Thyroxine replacement was only given for a month post-debulking thyroid surgery. She had hypotension (79/56 mm Hg), tachycardia (129 bpm) and muffled heart sounds. Chest X-ray showed globular enlargement of the cardiac silhouette with ‘’water bottle” configuration and right pleural effusion. Echocardiogram demonstrated early diastolic right ventricular collapse with a large pericardial effusion. The heart was seen swinging within the effusion, suggestive of cardiac tamponade. Urgent pericardiocentesis drained 200 mL of exudative serous fluid. There was no growth on pericardial fluid culture, and cytology was negative for malignant cells. Tests showed severe hypothyroidism (TSH >51.6 m IU/L and fT4 <3.2 pmol/L). Intravenous levothyroxine 50 mcg was given for two days. This was converted to thyroxine 100 mcg orally daily, then increased to 200 mcg daily based on serial thyroid function tests. She was discharged well after eight days of hospitalization. Her latest tests showed improved TSH (24.07 m IU/L) and fT4 (14.03 pmol/L). Conclusion A high index of suspicion is important for timely diagnosis of cardiac tamponade due to severe hypothyroidism, followed by prompt intervention. While it is a treatable cause of cardiogenic shock, it may be fatal if left unrecognized.